Predikce inzulin dependentního diabetes mellitus u dĕtských prvostupnových príbuzných diabetických pacientů - Cinek, O; Kolousková, S; Pechová, M; Sumník, Z; Sedláková, P; Bendukidze, N; Ivasková, E; Snajderová, M; Vavrinec, J (Casopis lekaru ceskych, 2001)
BACKGROUND: Individuals at risk for insulin dependent diabetes mellitus (IDDM) can be identified using a combination of genetic, immunological and metabolic markers. Our study was aimed at prediction of IDDM in a cohort of children having a first-degree relative with IDDM. METHODS AND RESULTS: In the period of three years, we investigated 208 non-diabetic children and adolescents, aged 10.0 +/- 5.3 (mean +/- SD), mostly siblings of diabetic children. The genetic risk was determined by the HLA-DQB1, -DQA1 genotyping and subtyping of the DRB1*04 alleles carried on the DQB1*0302 haplotypes. Insulitis was detected using a combination of autoantibody tests against three molecular-defined antigens (insulin, GAD65, IA-2). Prevalence of insulitis (defined as confirmed positivity of at least one autoantibody) was 9/208 (4.3%). In children carrying the IDDM highest-risk genotype (HLA-DQB1*0201-DQA1*05/DQB1*0302-DQA1*03), insulitis was almost 10 times more frequent (5/24, 21%) than in children with other genotypes (4/184, 2.2%, P = 0.003). In all subjects with insulitis, the first phase insulin response (FPIR) was determined by the intravenous glucose tolerance test. Three of the nine children had decreased FPIR, of whom two were later diagnosed with IDDM. None of the remaining children developed IDDM. CONCLUSIONS: We present the first IDDM prediction study in the Czech population, emphasising the utility of genetic risk investigation in the prediction scheme.
Keywords: Genotype; glukózový toleranční test; Female; dítě; ženské pohlaví; Adolescent; lidé; Glucose Tolerance Test; genotyp; glutamát dekarboxyláza; Glutamate Decarboxylase; genetická predispozice k nemoci; Genetic Predisposition to Disease; Humans; Risk Factors; Diabetes Mellitus, Type 1; Male; Autoantibodies; diabetes mellitus 1. typu; rizikové faktory; Child; Isoenzymes; mužské pohlaví; HLA-DQ Antigens; HLA-DQ antigeny; mladiství; izoenzymy; autoprotilátky